Ficus Plant Growing Technology - Nurmukhamedova, D. Sh.; Adilov, X. A.; Karshiev, A. E.; Qakhkhorova, O. F. (American Journal of Botany and Bioengineering, 2024)
The scientific article contains brief information about technologies for growing ficuss. Scientifically based information about the phases of growth and development of underground and aboveground vegetative organs of the ficus plant, as well as obtaining a high yield from them due to the technology of growing ficuss.